Wind tunnel tests and dynamic analysis of wind-induced response of a transmission tower on a hill. Issue 15 (November 2021) - Guo, Jian; Xiao, Changliang; Li, Jiantao
A hill with a lattice transmission tower presents complex wind field characteristics. The commonly used computational fluid dynamics (CFD) simulations are difficult to analyze the wind resistance and dynamic responses of the transmission tower due to structural complexity. In this study, wind tunnel tests and numerical simulations are conducted to analyze the wind field of the hill and the dynamic responses of the transmission tower built on it. The hill models with different slopes are investigated by wind tunnel tests to measure the wind field characteristics, such as mean speed and turbulence intensity. The study shows that the existence of a transmission tower reduces the wind speed on the leeward slope significantly but has little effect on the windward slope. To study the dynamic behavior of the transmission tower, a hybrid analysis procedure is used by introducing the measured experimental wind information to the finite element tower model established using ANSYS. The effects of hill slope on the maximum displacement response of the tower are studied. The results show that the maximum value of the response is the largest when the hill slope is 25° compared to those when hill slope is 15° and 35°. The results extend the knowledge concerning wind tunnel tests on hills of different terrain and provide a comprehensive understanding of the interactive effects between the hill and existing transmission tower regarding to the wind field characteristics and structural dynamic responses.